(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: the process of making the dough of bakery products, occupies an important place in traditional cooking. This process is one of the main stages that determines the quality of bread. When preparing bread dough, it is necessary to take into account a number of important factors. In this article, we will tell you about the main stages of the bread dough preparation process, ingredients, methods and some important tips.